Investigation into the stability of driving an automobile on the road pavement with ruts - Vansauskas, Vidmantas; Bogdevičius, Marijonas (Transport, 2009)
The article reviews the stability of an automobile on the road pavement with ruts. The problems of road safety depend on many factors. One of those is the quality of the road surface. Big heavy lorries deform the road surface causing ruts especially in the first line of the road. The article analyzes the influence of the geometry of ruts on the stability of the automobile. A mathematical model of a 3D automobile and the interaction between wheels and the road surface and the geometry of the road surface are presented. The mathematical criterion of the stability of the moving automobile on the road surface with ruts is laid down. The results of mathematical simulation and the criterion of the stability of the moving automobile (60 km/h) on the road surface depending on the depth of ruts are introduced. First published online: 27 Oct 2010